The 7 : Seven Wonders that will Change Your Life - Beck, Glenn and Ablow, Keith (New York Threshold Editions/Mercury Radio Arts, 2011)
Radio and television personality and #1 bestselling author Beck, together with psychiatrist Ablow, shares the inspirational story of the seven simple principles that changed Beck's life
Keywords: Self-realization -- Conduct of life -- Self-actualization (Psychology)